Case Report: A first case of desmin-related myofibrillar myopathy due to inheritance from a confirmed mosaic asymptomatic carrier - Vlaeminck, Jelle; Uyttebroeck, Sophie; De Schutter, Elke; Cordenier, Ann; Wellekens, Shauni; Ströker, Erwin; De Rooms, Kelly; Helsen, Christine; Hes, Frederik J.; Giron, Philippe (Frontiers in Genetics, 2025)
Desmin-related myofibrillar myopathy is a hereditary disorder caused by pathogenic variants in the DES gene (MIM*125660), altering desmin, a muscle-specific intermediate filament which is crucial for sarcomere integrity. This condition presents with skeletal myopathy, cardiomyopathy, and conduction abnormalities. Genetic counselling for index patients and their family members is complicated by variable expressivity, incomplete penetrance, and de novo occurrence. Mosaicism in asymptomatic parents can obscure inheritance patterns, particularly when low-grade mosaic variants in blood may be missed. In case of DES, mosaic carriership has not been described before. We describe a case of a 24-year-old female diagnosed with desmin-related myopathy due to a heterozygous pathogenic NM_001927.4 (DES):c.1216C>T, p.Arg406Trp variant. Cascade testing using targeted Sanger sequencing of her asymptomatic parents suggested the mother is a mosaic carrier of the pathogenic variant, which was confirmed though next-generation sequencing. The proband’s siblings did not carry the DES c.1216C>T variant. We report the first documented case of mosaic carriership of a pathogenic DES variant in an asymptomatic individual and subsequent inheritance by the offspring, leading to desmin-related myopathy. This report highlights the importance of cascade testing in hereditary disorders with a focus on mosaicism, even when the index’s biological parents are asymptomatic, and de novo emergence is suspected.